Investors' Risk Appetite and Global Financial Market Conditions - Gonzalez-Hermosillo, Brenda (Washington, D.C. : International Monetary Fund, 2008)
A structural vector autoregression model is developed to analyze the dynamics of bond spreads among a sample of mature and developing countries during periods of financial stress in the last decade. The model identifies and quantifies the contribution on bond spreads from global market conditions (including funding liquidity, market liquidity, as well as credit and volatility risks), contagion effects, and idiosyncratic factors. While idiosyncratic factors explain a large amount of the changes in bond spreads over the sample, global market risk factors are fundamental driving forces during periods of stress. The relative importance of the different risk factors changes substantially depending on the crisis episode. Contagion from emerging markets becomes small or non-existent when global financial market risks explicitly are taken into account.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet